Meal Timing Habits among Adults in Saudi Arabia: A Cross-Sectional Study - Sarah AlMuammar; Abeer Ahmed Algarni; Ftoon Badroun; Hanan Hassan Mushaeb; Raneem Khalid Abu Sadi; Areej Algarni (Advances in Public Health)
Background. The global rise in noncommunicable diseases, such as obesity, diabetes, and cardiovascular conditions, is a growing concern worldwide. Unhealthy dietary behaviors, specifically the habits of skipping breakfast and consuming late dinners, have emerged as key dietary behaviors with significant health implications. Methods. This cross-sectional survey-based study aimed to investigate meal-timing habits among adults in Saudi Arabia, with a particular focus on breakfast skipping. Results. The study included 2,262 participants, of whom 58.0% were women and 42.0% were men. It found that 31.4% of participants had less than three meals per day, and 74.2% reported snacking. Moreover, 16.8% of participants skipped breakfast and 18.9% of participants had late dinner. Females were found to be 1.3 times more likely to skip breakfast than males (OR = 1.3, 95% CI 1.0–1.6, P=0.04), while unemployed individuals were three times more likely to skip breakfast than those with full-time jobs (OR = 3.0, 95% CI 1.3–7.1, P=0.01). Conclusion. The study highlights a high prevalence of breakfast skipping and late evening dinners among adults in Saudi Arabia, particularly among females and unemployed individuals. Targeted interventions to promote healthy eating habits are needed to improve nutritional status and prevent chronic diseases in this population.